A breakthrough from 60 years ago: "General nature of the genetic code for proteins" (1961). Issue 1 (7th June 2021) - Cobb, Matthew
Abstract: In 1961, Francis Crick and Sydney Brenner, together with two Cambridge colleagues, published an article in Nature that used simple genetic experiments to demonstrate that the genetic code was almost certainly based on groups of three nucleotides. Six decades later, this article continues to be an inspiration to scientists due to its elegant argumentation and its use of simple, powerful experimentation to reveal fundamental truths about the organisation of living matter. This essay explores how and why the research was carried out, showing how the aims of the experiment gradually changed over time, and highlighting how the intense intellectual interactions between Crick and Brenner contributed to this model of scientific endeavour.